Mind and material engagement - Malafouris, L (Springer Netherlands, 2018)
Material Engagement Theory (MET), which forms the focus of this special issue, is a relatively new development within cognitive archaeology and anthropology, but one that has important implications for many adjacent fields of research in phenomenology and the cognitive sciences. In How Things Shape the Mind (2013) I offered a detail exposition of the major working hypotheses and the vision of mind that it embodies. Here, introducing this special issue, more than just presenting a broad overview of MET, I seek to enrich and extend that vision and discuss its application to the study of mind and matter. I begin by laying out the philosophical roots, theoretical context and intellectual kinship of MET. Then I offer a basic outline of this theoretical framework focusing on the notions of thinging and metaplasticity. In the last part I am using the example of pottery making to illustrate how MET can be used to inform empirical research and how it might complement new research in phenomenology and embodied cognitive science.